2001
DOI: 10.1128/jcm.39.5.1738-1745.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AfaE Adhesins Produced by Extraintestinal and Intestinal Human Escherichia coli Isolates: PCR Assays for Detection of Afa Adhesins That Do or Do Not Recognize Dr Blood Group Antigens

Abstract: adhesins) on the human decay-accelerating factor (DAF) as a receptor, and others (Afa/Dr؊ adhesins) do not. Thus, the afa operons detected in this study were characterized by subtyping the afaE gene using specific PCRs. In addition, the DAF-binding capacities of as-yet-uncharacterized AfaE adhesins were tested by various cellular approaches. The afaE8 subtype (Afa/Dr ؊ adhesin) was found to predominate in afa-positive isolates from sepsis patients (75%); it was frequent in afa-positive pyelonephritis E. coli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 47 publications
3
87
1
2
Order By: Relevance
“…Algunas de las proteínas implicadas en la virulencia de ECST, principalmente en algunas del T3SS, las subuniLas cepas de ECAD expresan adhesinas afimbriales (Afa) y adhesinas fimbriales (Dr). Estas adhesinas se encuentran en la superficie de la membrana externa de la bacteria, confiriendo el principal mecanismo de patogenicidad 122,123 . Se subdividen en dos clases, la típica Afa/DrECAD y la atípica Afa/DrECAD que tienen como características la misma organización genética y la unión al factor de aceleración (hDAF: human decayaccelerating factor) 124 .…”
Section: Patogeniaunclassified
“…Algunas de las proteínas implicadas en la virulencia de ECST, principalmente en algunas del T3SS, las subuniLas cepas de ECAD expresan adhesinas afimbriales (Afa) y adhesinas fimbriales (Dr). Estas adhesinas se encuentran en la superficie de la membrana externa de la bacteria, confiriendo el principal mecanismo de patogenicidad 122,123 . Se subdividen en dos clases, la típica Afa/DrECAD y la atípica Afa/DrECAD que tienen como características la misma organización genética y la unión al factor de aceleración (hDAF: human decayaccelerating factor) 124 .…”
Section: Patogeniaunclassified
“…DAEC strains were assigned to subgroups according to the scheme described by Le Bouguénec et al (34). Organisms that did not react with primers for any afa subtypes but reacted with the primer set for afaBC were classified as afaEX: the bacteria possessed genes amplified with primers for Afa/Dr but the gene was not identified as part of a particular subgroup.…”
Section: Il-8 Induction Testmentioning
confidence: 99%
“…French groups have continued to investigate these Afa-positive DAEC and have provided information regarding their molecular bacteriology (2,(14)(15)(16)(31)(32)(33)(34). Furthermore, Bétis et al (3,4) found that two DAEC strains induced interleukin-8 (IL-8) in human colonic epithelial cell line, T84.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these adhesins differ in sequence, they all bind to the third CCP domain of DAF with the exception of AfaE-VII and AfaE-VIII (18). Two of the Afa/Dr adhesins, AfaE-III and DraE, differ in sequence by only three amino acids but possess significantly different properties.…”
mentioning
confidence: 99%